2019
DOI: 10.1002/job.2367
|View full text |Cite
|
Sign up to set email alerts
|

Moral emotions: A review and research agenda for management scholarship

Abstract: Summary By discussing “families” of moral emotions, we synthesize and review the moral emotions literature in an effort to advance organizational scholarship. First, we broadly discuss “what constitutes a moral emotion?” Second, we critically examine each family of moral emotions. We discuss key controversies and debates, particularly in terms of construct overlap, and provide recommendations. Third, we review scholarly work on each family of moral emotions in the workplace and offer ideas for future research.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 216 publications
(361 reference statements)
5
106
0
1
Order By: Relevance
“…Besides competence, selfevaluation depends on meeting moral standards (for instance, being fair to colleagues). Meeting moral standards is closely tied to self-conscious emotions such as shame, guilt, and pride (Tangney & Tracy, 2012), which are regarded as part of moral emotions (Gausel & Leach, 2011;Greenbaum et al, 2019) but may also occur in the context of task-related failures and successes (Kim & Kammeyer-Mueller, 2018). Adequacy of performance and moral behavior constitute the self-evaluation part of the SOS model; not meeting one's standards in this domain induces feelings of insufficiency and is therefore called "Stress through Insufficiency" (SIN).…”
Section: Stress-as-offense-to-self (Sos)mentioning
confidence: 99%
“…Besides competence, selfevaluation depends on meeting moral standards (for instance, being fair to colleagues). Meeting moral standards is closely tied to self-conscious emotions such as shame, guilt, and pride (Tangney & Tracy, 2012), which are regarded as part of moral emotions (Gausel & Leach, 2011;Greenbaum et al, 2019) but may also occur in the context of task-related failures and successes (Kim & Kammeyer-Mueller, 2018). Adequacy of performance and moral behavior constitute the self-evaluation part of the SOS model; not meeting one's standards in this domain induces feelings of insufficiency and is therefore called "Stress through Insufficiency" (SIN).…”
Section: Stress-as-offense-to-self (Sos)mentioning
confidence: 99%
“…While several researchers have suggested that emotions can help individuals who want to make their decision making more ethical (Wang et al, 2014; Zhong, 2011), few studies have examined the role of moral emotions in conjunction with hedonic emotions. Studies examining moral emotions have tended to use a single moral emotion and a single hedonic emotion (e.g., guilt vs. anger, Motro, Ordóñez, Pittarello, & Welsh, 2018), or taken a families approach to understanding moral emotions (see Greenbaum et al, 2019; Tangney et al, 2007, for review). Our study draws on MFT (Graham et al, 2013) and theories on anticipated pleasure (Mellers et al, 1999) to demonstrate the internal conflict created by mixed emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Third-party anger has also been associated with victim-directed support (Hershcovis & Bhatnagar, 2017) and changing harmful organizational practices (Lindebaum & Geddes, 2016). More recently, management scholars have also identified moral emotions as relevant antecedents to organizational behavior (Greenbaum, Bonner, Gray, & Mawritz, 2019).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…The first article is a review of moral emotions by Greenbaum, Bonner, Gray, and Mawritz (). It has been 17 years since Haidt published his seminal review of moral emotions, where he classified moral emotions into four families: other‐praising, other‐suffering, other‐condemning, and self‐condemning (see Haidt, ).…”
Section: Preview Of Articles In This Issuementioning
confidence: 99%
“…In the next article, Razinskas and Hoegl () review the stressor research in teams, broadening our horizons by deviating from the dominant focus on individual level stressors, to instead highlight a multi‐level perspective. Given the prevalence of teams in workplaces today, and the increasing levels of stress in the workplace (see Pfeffer, ), this is a most timely and relevant review. This article offers an important conceptual grounding for how and why stimuli in this social environment influence both the team as a collective, and individual members within the team.…”
Section: Preview Of Articles In This Issuementioning
confidence: 99%